Fabrication & properties of aluminium-silicon carbide (A1/SiC) composite material - Farah Fazira, Kamaruzaman (2015)
A composite material is the material that consisting of two or more chemically or physically specific phase. The reinforcing component is distributed in continuous or matrix components. When the matrix is metal, the composite is namely metal matrix composite (MMC). In this research study, the metal matrix used is aluminium while the fiber material used is silicon carbide. So, when these two distinct materials combined it will form as aluminium-silicon carbide (Al/SiC) composite. The main objective of this research is to study the behavior of Al/SiC composite in different ceramic composition under various compaction loads. The fabrication of homogenous Al/SiC composite material consists several processes in powder metallurgy technique. The main step of powder metallurgy are mixing and blending, compacting and sintering. The mixing and blending process begin with prepare both powder material which is varies in weight percentage of SiC. After that, the mixed powders were pressed through compaction process in a 30mm diameter cylindrical steel die by using the hydraulic press machine under three different compaction loads. And lastly, all the specimens were sintered in a furnace to a fixed temperature, 500°C. This research study is completed by the characterization and mechanical testing. The specimens are characterized and the microstructures of the composites were studied by using the optical microscope. After that, the hardness of composites was tested by using Vickers Micro-Hardness Testing machine. The conclusion gained from this study is the different ceramic composition under various compaction loads plays significant influences in determining the performances of the Al/SiC composite material. The differences in ceramic compaction under various compaction load affect the data gained in density differentiate before and after sintering process, hardness test and microstructure in Al/SiC composite material.